Next-generation particle sizing: interferometric nanoparticle tracking analysis (iNTA) - Blessing, Martin; Kashkanova, Anna D.; Gemeinhardt, André; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2022)
Resolving polydispersions in the nanometer regime remains a challenge for state-of-the-art particle sizers. By combining nanoparticle tracking analysis with interferometric scattering microscopy, we precisely estimated the size and refractive index of (in)organic particles in polydispersions.
CRIS-Team Scopus Importer:2023-03-27